THE PROBLEMS OF BRINGING RUSSIAN TRADE POLICY IN LINE WITH WTO REQUIREMENTS - M. A. Petrova (Vestnik MGIMO-Universiteta)
The article analyzes the role of trade policy in ensuring the competitiveness of the automotive industry – one of the most sensitive to the changes of economic conditions and important for providing national economic security – and finding a balance between the need to regulate the internal market and the implementation of the commitments under WTO. The analyze of the current condition of the Russian automotive industry has shown that, despite the low share in the world production and exports, Russia has a great potential for growth, mainly due to the unsaturated domestic market. It is proved, that the development of the automotive industry as one of the innovative industries in the country has all the necessary terms. Moreover, the priority areas for the development of the automotive industry include, first of all, the creation of a full range production with foreign investment. Measures of attracting and regulating FDI received much attention due to their relationship with the instruments of trade policy, as the production of capital goods, particularly automobiles, require imports of components, and FDI, in turn, promote the export of finished products. The commitments taken by Russia in the automotive industry include reduction of duties on imported cars, the renegotiation of investment programs and rules for the functioning of special economic zones. At present, the most acute question is car recycling tax, which has led to a trade dispute with the European Union, and may lead to countervailing measures against Russian goods. Considering WTO rules, recommendations on the use of the most effective instruments of foreign policy, aimed at improving the competitiveness of the Russian automotive industry, were made, including the rationalization of import and the attraction of new technologies due to the diversification of customs duties on certain groups of automotive components, lowering income taxes, a gradual decrease of the fiscal functions of the customs tariff; the stability and transparency of the instruments of trade policy and simplification of customs procedures.